Experimental analysis of an alternator excited with photovoltaic cells for small power plants - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2011)
In this study, an automatic voltage regulator fed by photovoltaic (PV) cells was designed for use in small power alternators. The design aimed to increase the energy output of the alternator and to ensure necessary current output from the PV cells to support the synchronous generator excitation system. For energy transformation from small renewable energy sources, designers have favored the use of alternators that produce higher quality electric power, rather than asynchronous generators. We also address the designed system's suitability for real-life application, examining the steady-state performance of the photovoltaic cell excited alternator (PVCEA) with various loads and its behavior in sudden load and fault situations.
Keywords: Photovoltaic cell; alternator; small power plants; synchronous generator; fault analysis; SYSTEM